Perbedaan Prestasi Belajar Pebelajar Yang Diajar Dengan Menggunakan Problem Solving dan Ekspositori Yang Memiliki Modalitas Belajar Berbeda - Azhar, Imam (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2016)
Learning strategy that tested its effectiveness in this research is problem solving strategy juxtaposed with expository in course of learning strategy in semester V Department of PAI STAIDRA. The research problems proposed are: 1) Is there any difference in learning achievement between the learners group treated using the learning strategy of the PS and the learning group using the expository learning strategy on the learners?, 2) Is there a difference in the learning achievement of learners who have different learning modalities on the learners ?, and 3) Is there an interaction between learning strategies and learning modalities to learning achievement learners? This research uses pretest & posttest design nonequivalent control group design with 3x2 factorial variance analysis. The result of 3x2 factorial ANOVA test shows that 1) The result of the data test using the two path ANOVA obtained the price of F equal to 22.342 and the significance level of 0.000. Because the level of significance <0.05, then Ho is rejected and means Ha accepted. This means that there are differences in learning achievement learners who are treated using learning strategies PS and groups of learners using expository learning strategies. 2) The test results using ANOVA obtained the price of F for 1727 and the level of significance of 0.186. Because the level of significance> 0.05, then Ho accepted and Ha means rejected. This means there is no difference in learning achievement learners based on learning modalities. 3) The results of data testing obtained price F of 0,560 and significance level 0.574. Because the level of significance> 0.05, then Ho accepted and Ha means rejected. That is, there is no interaction between learning strategies (PS and expository) and Modality of learning to learning achievement.